Understanding the Association Between Intolerance of Uncertainty and Problematic Smartphone Use: A Network Analysis - Liu, Chang; Ren, Lei; Li, Kuiliang; Yang, Wei; Li, Ye; Rotaru, Kristian; Wei, Xinyi; Yücel, Murat; Albertella, Lucy (Frontiers in Psychiatry, 2022)
Background: Existing research has demonstrated that intolerance of uncertainty (IU) is associated with problematic smartphone use (PSU). However, little is known about how different IU components such as uncertainty-related beliefs, emotions, and behaviours may impact on different PSU symptoms. Methods: Extending previous research, the current study examined the specific associations between IU components and PSU symptoms via a symptom-level network approach. A regularized partial network consisting of different IU components and PSU symptoms was estimated among 1,849 Chinese university students. We examined pathways and influential nodes (i.e. central components/symptoms and bridge components/symptoms) within the IU-PSU network. Results: The strongest pathway linking IU and PSU was between emotional reactions to uncertainty and coping-motivated smartphone use. Importantly, emotional reactions towards not having enough information (a reflection of emotional reactions to uncertainty) may act as both a central and a bridge component in maintaining the whole IU-PSU network. Conclusions: The results are in line with the core tenets of the compensatory Internet use theory and highlight that PSU may be a coping response for negative emotions derived from uncertainty. Finally, the current findings highlight the potential of interventions targeting intolerance of uncertainty for reducing PSU.